Coronavirus Disease (COVID-19) Outbreak among Islamic Missionaries in Terengganu state of Malaysia in 2020. - Ning, Goh Soo; Awang, Hafizuddin; Omar, Ahmad Fuad; Jaafar, Juhaida; Muda, Fatimah; Ahmad, Mohd Hanief; Embong, Kasemani; Yunus, Nor Azimi (International Journal of Human and Health Sciences (IJHHS), 2021)
Background: Malaysia experienced an outbreak of COVID-19 after Islamic missionaries returned from religious gathering in Sri Petaling Mosque, Kuala Lumpur. The outbreak extended to the state of Terengganu which also resulted in an outbreak in a private Islamic institution known as BKMQ (an anonymized name) in Kuala Terengganu District. Materials and Methods: A descriptive cross-sectional study was conducted to describe the characteristics of COVID-19 cases and the experience of COVID-19 outbreak containment in BKMQ. Results: There were six individuals diagnosed with COVID-19 in BKMQ. Majority of them were male (83.3%), in the age group of 20 to <40 years old (50.0%) and had fever as their symptom (50.0%). The time of last exposure to diagnosis among majority of cases were 12 days, and majority of cases (66.6%) stayed in hospital between 20 days to less than 40 days. Conclusion: The transmission of virus was postulated to be through household exposure and vehicle sharing. Prompt action, immediate lockdown and inter-agencies collaboration were the key factors in successfully controlling the spread of COVID-19 in the institution and community. International Journal of Human and Health Sciences Vol. 05 No. 04 October’21 Page: 491-498